The Comprehensive Systematic Review of Association of Automated Insulin Delivery Systems to Time-in-Range Improvement in DM Pediatric - Nadya Virana Putri; Selvia Rahayu; Ningrum Jayanti (International Medical Journal Corp. Ltd, 2026)
Introduction: Automated insulin delivery (AID) systems represent a transformative advancement in the management of type 1 diabetes (T1D) in pediatric populations. These systems aim to improve glycemic control by automating insulin adjustments based on continuous glucose monitoring, thereby increasing time-in-range (TIR) and reducing hypoglycemia. However, comprehensive evidence on their efficacy across diverse pediatric age groups, baseline glycemic profiles, and prior therapy methods remains essential for clinical implementation. Methods: This systematic review synthesized evidence from 80 studies, including randomized controlled trials, meta-analyses, single-arm studies, and observational studies conducted between 2010 and 2025. Inclusion criteria focused on pediatric populations (0–18 years), AID interventions, TIR outcomes, and controlled study designs. Data extraction covered AID system details, population characteristics, study design, control comparisons, TIR outcomes, safety metrics, and key findings. Results: AID systems consistently improved TIR across pediatric populations, with meta-analyses reporting mean improvements of 8.70% to 11.38% (Baoqi Zeng et al., 2023; L. Hespanhol et al., 2023). Individual trials showed TIR gains of 6.7% to 19.1%, translating to 2.6 to 3.7 additional hours/day in target range. Greater improvements were observed in those with higher baseline HbA1c (Abraham et al., 2024) and in patients transitioning from multiple daily injections (MDI) to AID (G. Petrovski et al., 2022). Safety outcomes were favorable, with rare severe hypoglycemia or diabetic ketoacidosis events and reduced time below range. Discussion: The evidence supports AID systems as effective and safe across all pediatric age groups. Improvements were influenced by baseline glycemic control, prior therapy, age, system settings, and user engagement. AID also demonstrated potential to reduce healthcare disparities, with significant benefits in under-resourced populations. Virtual initiation and structured protocols further enhance accessibility and outcomes. Conclusion: AID systems significantly and safely improve TIR in pediatric T1D, with durable benefits over time. Implementation should be encouraged across all pediatric age groups, with particular attention to patients with suboptimal baseline control and those transitioning from MDI. Future research should focus on long-term outcomes, psychosocial impacts, and equitable access.